**Solve the exponential equation: **`e^(6x^2-1)=13`

### 1 Answer | Add Yours

The equation `e^(6x^2 - 1) = 13` has to be solved.

Take the natural log of both the sides.

`6x^2 - 1 = ln 13`

=> `6x^2 = 1 + ln 13`

=> 6x^2 = ln(13 + e)

=> `x^2 = (ln(13 + e))/6`

=> `x^2 = ln(13 + e)^(1/6)`

=> `x = sqrt(ln(13 + e)^(1/6))` and x = `-sqrt(ln(13 + e)^(1/6))`

**The solution of the equation is x = `sqrt(ln(13 + e)^(1/6))` and x = **` -sqrt(ln(13 + e)^(1/6))`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes